Successful treatment of multisite hemorrhage by several methods in brain metastasis of choriocarcinoma: A case report. Issue 21 (May 2018) - Ren, Zhen; Yu, Li; Xie, Mengnv; Liang, Yiyi; Zhu, Fang; Huang, Rui; Zhang, Zhibang; Fu, Chun
Abstract: Rationale: Brain metastasis of choriocarcinoma is a highly malignant gestational trophoblastic neoplasia (GTN) and has a notoriously poor prognosis. Hemorrhagic choriocarcinoma lesions may lead to life-threatening conditions also. Treatment of brain metastases of choriocarcinoma with hemorrhage in multiple sites is very difficult in clinical practices. A patient has been successfully treated in our hospital, which provides as clinical references for this difficulty in treating brain metastases of choriocarcinoma with hemorrhage in multiple sites. Patient concerns: A 28-year-old patient with gravida 2, para 0 was admitted in our hospital for amenorrhea, vaginal bleeding, and lower abdominal pain. Diagnoses: The patient was diagnosed as choriocarcinoma FIGO stage IV and the score of the Prognostic Scoring Index modified by the WHO was 15. Interventions: The patient received multiagent chemotherapy (EMACO regimen) soon after the diagnosis of choriocarcinoma with brain metastasis. During the therapy, the patient was given 3 different methods of treatment for metastatic site hemorrhage. An emergency surgery was performed to control massive bleeding from the metastatic lesions of broad ligament. Blood transfusions were given to treat acute left pulmonary hemorrhage. Uterine artery embolization (UAE) was performed to treat increased uterine bleeding. Outcomes: The patient achieved remission after 9 cycles of chemotherapy. She has been followed up for 14 months with no signs of tumor recurrence. Lessons: The diagnosis of choriocarcinoma may be difficult, especially in the setting with the limit of medical resources. The application of various diagnostic techniques such as x-ray, computed tomography, and magnetic resonance imaging is helpful for evaluating the patient's condition.